Functional Update of the Auxiliary Proteins PsbW, PsbY, HCF136, PsbN, TerC and ALB3 in Maintenance and Assembly of PSII - Plöchinger, Magdalena; Schwenkert, Serena; von Sydow, Lotta; Schröder, Wolfgang P.; Meurer, Jörg (Frontiers in Plant Science, 2016)
Assembly of Photosystem (PS) II in plants has turned out to be a highly complex process which, at least in part, occurs in a sequential order and requires many more auxiliary proteins than subunits present in the complex. Owing to the high evolutionary conservation of the subunit composition and the three-dimensional structure of the PSII complex, most plant factors involved in the biogenesis of PSII originated from cyanobacteria and only rarely evolved de novo. Furthermore, in chloroplasts the initial assembly steps occur in the non-appressed stroma lamellae, whereas the final assembly including the attachment of the major LHCII antenna proteins takes place in the grana regions. The stroma lamellae are also the place where part of PSII repair occurs, which very likely also involves assembly factors. In cyanobacteria initial PSII assembly also occurs in the thylakoid membrane, in so-called thylakoid centers, which are in contact with the plasma membrane. Here, we provide an update on the structures, localisations, topologies, functions, expression and interactions of the low molecular mass PSII subunits PsbY, PsbW and the auxiliary factors HCF136, PsbN, TerC and ALB3, assisting in PSII complex assembly and protein insertion into the thylakoid membrane.